2021
DOI: 10.1186/s12870-021-02877-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolic profiling and transcriptome analysis of pigment accumulation in Lonicera japonica flower petals during colour-transition

Abstract: Background Plants have remarkable diversity in petal colour through the biosynthesis and accumulation of various pigments. To better understand the mechanisms regulating petal pigmentation in Lonicera japonica, we used multiple approaches to investigate the changes in carotenoids, anthocyanins, endogenous hormones and gene expression dynamics during petal colour transitions, i.e., green bud petals (GB_Pe), white flower petals (WF_Pe) and yellow flower petals (YF_Pe). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…From opening to mature, the stigma color presents successively green, light-purple red, dark-purple red, dark purple ( Figure 1A ). Chlorophylls, carotenoids, and anthocyanins are three chemically diverse groups of pigments and the core members in flower color formation ( Xue et al, 2020 ; Xia et al, 2021 ). Our present work showed that the stigma appeared green at the first stage (S1) when the chlorophyll content was higher than the other two pigments, gradually turning red and purple as the anthocyanin and carotenoid content increased (S2 to S3), and eventually getting dark purple due to the reduction of carotenoid content and sharp increase of anthocyanin content of from S3 to S4 ( Figures 1A–D ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From opening to mature, the stigma color presents successively green, light-purple red, dark-purple red, dark purple ( Figure 1A ). Chlorophylls, carotenoids, and anthocyanins are three chemically diverse groups of pigments and the core members in flower color formation ( Xue et al, 2020 ; Xia et al, 2021 ). Our present work showed that the stigma appeared green at the first stage (S1) when the chlorophyll content was higher than the other two pigments, gradually turning red and purple as the anthocyanin and carotenoid content increased (S2 to S3), and eventually getting dark purple due to the reduction of carotenoid content and sharp increase of anthocyanin content of from S3 to S4 ( Figures 1A–D ).…”
Section: Discussionmentioning
confidence: 99%
“…Flower color plays an essential function in plant ecology and evolution by attracting animal pollinators ( Grotewold, 2006 ), being a central feature of plant observation, and having a significant ornamental function ( Xue et al, 2020 ). Due to the importance of color formation in angiosperm, especially in the ornamental plant, the biosynthetic pathways of pigment in color formation have been widely reported ( Grotewold, 2006 ; Chen et al, 2016 ; Xia et al, 2021 ). Three chemically distinct groups of pigments, chlorophylls, carotenoids, and anthocyanins are widely distributed in plants and are the major pigments in flower color formation ( Xue et al, 2020 ; Xia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as drought, temperature, salinity, and phytohormones extensively contribute to plant growth and development, inducing various morphological, physiological, and biochemical responses ( Utsumi et al, 2019 ; Li F. et al, 2020 ). Metabolomics data can connect genomic and phenotypic manifestations ( Xia et al, 2021 ). For plants, survival in different conditions requires substantial metabolic changes, which are reflected by extensive transcriptional level changes that occur during exposure to stress ( Janiak et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, analysis of the metabolomics combined with the transcriptome had widely used in revealing the mechanisms of many important physiological processes ( Scossa, Alseekh & Fernie, 2021 ; Xia et al, 2021 ; Zou et al, 2021 ). In research on Lonicera japonica Thunb, integrated metabolomics and transcriptome analysis of pigment accumulation in Lonicera japonica flower petals during colour transition revealed changes in key pigments and related biosynthesis genes associated with petal colour transitions ( Xia et al, 2021 ). Besides, in our previously research, through integrated metabolomics and transcriptome methods, we analyze the molecular mechanism of flavonoid biosynthesis under MeJA treatment in safflower ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%